KONFLIK PERAN, DUKUNGAN SOSIAL PASANGAN, DAN PRESTASI KERJA Di PT. SARIWARNA ASLI TEXTILE BOYOLALI - Errin Setyowati; Ari Pradhanawati (Universitas Diponegoro, 2019)
At PT. Sariwarna really needs female workers, especially women workers because spinning and weaving requires precision, diligence and patience, the Chairperson of the Trade Union said so. The head of the HRD also said that married women had better performance compared to unmarried female workers, this was because married female workers had worked for years and were already accustomed to the existing workload. The purpose of this study is to find out the influential role conflict on work performance and to find out the social support of the couple influences the role conflict in married women who have children at PT. Original Textile Sariwarna. To answer the problems and objectives of the study using structural functionalism theory popularized by Robert K. Merton, as a study in analyzing the existing problems, namely the dual role of wives in the family. The results of the study related to the purpose of the study which wanted to explain the influential role conflict on work performance from the results of this study were indeed role conflict influenced work performance but only a few informants experienced it. Furthermore, namely to explain the social support of the couple influencing the role conflict, the results of this study show that the social support of couples is very important when female workers experience role conflict. The latter, namely the social support of the couple influences the work performance of the results of the study shows that it greatly influences work performance and the social support of the couple plays an important role.